The effect of dentinal fluid flow during loading in various directions - simulation of fluid- structure interaction - Su, Kuo-Chih (2013)
Objectives This study uses a fluid–structure interaction (FSI) simulation to evaluate the fluid flow in a dental intrapulpal chamber induced by the deformation of the tooth structure during loading in various directions.